The Economics of a VAT Cut in the Standard Keynesian Framework: A Possible Anti-Crisis Measure? - VASILEV, Aleksandar (Theoretical and Practical Research in Economic Fields, 2025)
The standard textbook treatment of expansionary fiscal policy at intermediate macroeconomics level (and specifically implemented via a tax rate reduction), e.g ., Blanchard (2021), Burda and Wyplosz (2023), or even at an advanced level, e.g ., Romer (2018)- only considers income tax cuts affecting the economy through the consumption function, by increasing the level of disposable income. In this paper we introduce VAT in the Keynesian cross framework and study the effects of a cut in the VAT rate. Under certain conditions, such as a relatively high pre-existing level of the VAT rate, a relatively low (proportional) income tax rate, and a sufficiently high MPC (marginal propensity to consume), a cut in the VAT rate has a positive effect on output and thus can be potentially used as a short-term anti-crisis measure. Interestingly, we find that the stimulus effect dissipates once we allow for an open economy, as people spend a substantial part of their income on imported products, i.e , when the MPI (marginal propensity to import) is high. Our findings are novel in literature and could be of interest both to policy makers, as well as economists interested in economic education and teaching.